1997
DOI: 10.1159/000006742
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Hypoxemia without Congestive Heart Failure in Patients Presenting with Acute Myocardial Infarction

Abstract: This study investigated the clinical significance of hypoxemia without apparent clinical congestive heart failure in patients with acute myocardial infarction (AMI). Sixty-two patients with AMI of the Killip group I and Forrester subset I state were stratified into a hypoxemia group and a normoxemia group. The increase in the neutrophil count and the severity of the coronary artery disease as graded by Gensini’s score were significantly higher in the hypoxemic group. The cardiac index was lower in hypoxemic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Hypoxemia is a state often encountered in patients suffering from acute or chronic lung and cardiovascular diseases and may contribute to the poor, long-term outcome of patients presenting with acute myocardial infarction [10] or multiple injuries [8]. In many clinical disorders potentially complicated by hypoxemia, the severity of the disease correlates with the increased number of primed and/or activated PMN in circulation [4][5][6]28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxemia is a state often encountered in patients suffering from acute or chronic lung and cardiovascular diseases and may contribute to the poor, long-term outcome of patients presenting with acute myocardial infarction [10] or multiple injuries [8]. In many clinical disorders potentially complicated by hypoxemia, the severity of the disease correlates with the increased number of primed and/or activated PMN in circulation [4][5][6]28].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxemia is frequent in patients suffering from respiratory and cardiovascular diseases [7], as well as in life-threatening conditions such as following multiple injuries [8], ARDS [4], septic shock [9], and myocardial infarction [10]. However, whether moderate hypoxemia, as seen frequently in patients, contributes to sensitize the PMN to enhanced functional responses remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Although some investigators have suggested that inducible systemic hypoxia may facilitate recovery of the infarcted myocardium [7,8], hypoxia is generally thought to aggravate hypoxemia [9]; in turn, hypoxemia is known to induce more severe cardiac dysfunction after MI [10]. Accordingly, it remains unclear whether hypoxia beneficial or detrimental to patients with MI.…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure and mortality is significantly increased by tissue necrosis from hypoxia. Myocardial injury can result from hypoxemia, where a decrease in oxygen partial pressure (pO2) is observed (103,104). Under normal physiological conditions, hypoxia induces gene expressions that initiate erythropoiesis, activating the maturation and proliferation of hematopoietic progenitor cells (hematopoietic stem cells) present in peripheral blood and bone marrow (105).…”
Section: Refractory Hypoxemia and Hypoxiamentioning
confidence: 99%